(3cTa GdhLhg GdZQ deYGfj fXe GdOQs - (3YR GdOjf eMehO Hf Ydj GdcGTGfjs ((3YHO GdbGOQ Hf YeQ Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi adb HbOQJg UHM GdhLhO Yf ZSb GdYOe aLYdg BjI eHUQI djbje Ydjg OdjdkG haJb HMceJg QJb GdLeY ai Yjf GdbOe eaUd cd TF JaUjdkG s
(3BNQgG (B:s
(3hgPG GdcdGe eMehd Ydi McGjJg HdSGf GdLeY Yf GdebGe GdeMeOi Udi Gddg Ydjg hSde ceG SHb eQGQkG hgPG BNQ eG CQOfG EjQGOg ai gPG GdeNJUQ ef TQM GdbUjOI HYhf Gddg GdebJOQ Je TQM gPg GdbUjOI GdeHGQcI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs